Sharing Session Seleksi Penerimaan Mahasiswa Baru (SNPMB) 2023 Untuk Calon Mahasiswa Baru Di SMA Negeri 1 Kefamenanu NTT - Meiva Marthaulina Lestari Siahaan; Zulkaidah Nur Ahsan; Hermina Disnawati; Lidwina Felisima Tae (Jurnal Nusantara Berbakti, 2023)
This service is based on changes in the mechanism and substance of the implementation of National Selection for Student Admissions (SNPMB). This transition is something new for prospective students and if prospective students do not understand it, it will 0certainly have a bad impact on the readiness of prospective students in participating in the implementation of UTBK-SNBT. The procedure for implementing the service is a sharing session on the implementation of SNPMB 2023, introduction and discussion of the 2023 UTBK-SNBT model questions, as well as an initial ability test on the representation of the 2023 UTBK-SNBT question model based on the latest UTBK-SNBT sub-matter. Then the socialization participants will be given a test to measure their knowledge of the SNPMB 2023 mechanism after the provision of SNPMB 2023 material. The results of this service activity are that more than 90% of prospective university students at SMA Negeri 1 Kefamenanu have understood the mechanism for implementing SNPMB 2023 after participating in the sharing session, based on the ability test, prospective university students do not fully understand the 2023 UTBK-SNBT model questions, and based on the results of the questionnaire, more than 90% of sharing session participants gave a good response to this activity. The results of this activity are important as a measure of understanding of the SNPMB 2023 mechanism and provide an overview of the initial ability of prospective students to answer UTBK 2023 model questions so that follow-up can be known in accordance with these abilities.